Different Persistence of the Cellular Effects Promoted by Protein Kinase CK2 Inhibitors CX-4945 and TDB. (19th October 2015) - Girardi, Cristina; Ottaviani, Daniele; Pinna, Lorenzo A.; Ruzzene, Maria
Abstract : We compare the cellular efficacy of two selective and cell permeable inhibitors of the antiapoptotic kinase CK2. One inhibitor, CX-4945, is already in clinical trials as antitumor drug, while the other, TDB, has been recently successfully employed to demonstrate the implication of CK2 in cellular (dis)regulation. We found that, upon treatment of cancer cells with these compounds, the extent of inhibition of endocellular CK2 is initially comparable but becomes significantly different after the inhibitors are removed from the cellular medium: while in CX-4945 treated cells CK2 activity is restored to control level after 24 h, in the case of TDB it is still strongly reduced after 4 days from removal. The biological effects of the two inhibitors have been analyzed by performing clonogenic, spheroid formation, and wound-healing assays: we observed a permanent inhibition of cell survival and migration in TDB-treated cells even after the inhibitor removal, while in the case of CX-4945 only its maintenance for the whole duration of the assay insured a persisting effect. We suggest that the superiority of TDB in maintaining kinase activity inhibited and perpetuating the consequent effects is an added value to be considered when planning new therapies based on CK2 targeting.